Caracterización bioquímica de razas nativas de maíz de Argentina en ensayos de jardín común - Dudzien, Tatiana L.; Defacio, Raquel Alicia; Paniego, Norma Beatriz; Lia, Verónica V.; Dominguez, Pia Guadalupe (Instituto Nacional de Tecnología Agropecuaria (INTA), 2024)
Poster